Performance Comparison Between Texel and Garut Sheep Fed with the Same Feed Formula - Murtanto, Ex Samuel; Sukaryani, Sri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Sheep farming plays a strategic role in providing animal protein sources in Indonesia. One of the challenges often encountered in fattening is determining which sheep species will best respond to the same feed formula. This study aimed to compare growth performance and feed utilization efficiency between male Texel and Garut sheep fed with identical feed compositions. A total of 12 male sheep aged 9–10 months, consisting of 6 Texels and 6 Garuts, were reared individually for 28 days. The diet consisted of 60% concentrate and 40% forage, with water provided ad libitum. Observed parameters included daily feed intake (g/head/day), average daily gain (ADG, g/head/day), and feed conversion ratio (FCR). Data were analyzed using an independent samples t-test at a 5% significance level. The results showed that Texel sheep had higher daily feed intake (921.25 g) compared to Garut (879.76 g), greater ADG (70.53 g vs. 56.65 g), and lower FCR (13.07 vs. 15.54). All differences were statistically significant (p < 0.05). These findings indicate that Texel sheep outperform Garut sheep in both growth rate and feed conversion efficiency, making them more suitable for intensive fattening programs based on locally available feed resources.